TRANSPARENCY OF MONEY AND BUILDING TAX PAYMENT MANAGEMENT IN PREVENT FRAUD(Case Study in Balekambang Village, South Nagrak Village, North Nagrak Village, and Pawenang Village Nagrak District Sukabumi District) - Pratami, Andi Rahmina (Universitas Nusantara PGRI Kediri, 2020)
The problem discussed in this study is the transparency of land and building tax management in preventing fraud in Balekambang Village, Nagrak District, Sukabumi District. This study aims to determine the effect of transparency on fraud. The method used in this study is a quantitative method. The samples in this study were 43 people using saturated samples because the study sample was less than 100. The results showed that the transparency of the management of land and building tax payments in Balekambang Village, South Nagrak Village, North Nagrak Village, and Pawenang Village the results did not affect someone in committing fraud.